2005
DOI: 10.3171/spi.2005.2.4.0441
|View full text |Cite
|
Sign up to set email alerts
|

New treatment of lumbar disc herniation involving 5-hydroxytryptamine2A receptor inhibitor: a randomized controlled trial

Abstract: Object. Serotonin or 5-hydroxytryptamine (5-HT) is a chemical mediator associated with nucleus pulposus—induced radiculopathy. Inhibition of 5-HT receptors may potentially alleviate symptoms in patients with lumbar disc herniation. This prospective randomized controlled study was performed to evaluate the efficacy of the 5-HT2A receptor inhibitor in the treatment of symptomatic lumbar disc herniation. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…10 Kanayama et al 9 studied the efficacy of 5-HT2A receptor antagonists in patients with symptomatic lumbar disc herniation with and without disc extrusion. They reported that the 5-HT2A receptor antagonists were effective in treatment of patients without disc extrusion while they were not effective in patients with extruded disc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Kanayama et al 9 studied the efficacy of 5-HT2A receptor antagonists in patients with symptomatic lumbar disc herniation with and without disc extrusion. They reported that the 5-HT2A receptor antagonists were effective in treatment of patients without disc extrusion while they were not effective in patients with extruded disc.…”
Section: Discussionmentioning
confidence: 99%
“…8 Indeed, serotonin specific reuptake inhibitors have been successfully used to treat CLBP. 9,10 Moreover, it was reported that an important portion of CLBP patients have concomitant fibromyalgia. 11 However, to date, the abnormalities in the serotonergic system and the variation in genes that are involved in 5-HT synthesis and potentially associated with the extent of the pain have not been studied in patients with CLBP.…”
mentioning
confidence: 99%
“…Three studies 161,172,226 did not report any pain, global or CSOM data. 161,172,226 Fifteen studies compared different types of non-opioids 223,227,229,[231][232][233][234][235][236][237][238][239][240][241] (seven of which were three-arm studies 57,215,223,227,229 and two studies of which were reported in a single publication 223 ). The types of non-opioids being compared are presented in Table 45b but the findings are not considered further.…”
Section: Description Of Non-opioids Studiesmentioning
confidence: 99%
“…The incidence of adverse reactions in our study was 4.83%, which is not significantly higher than the combined incidence in the clinical trials and postmarketing surveillance (2.23%; 107/4,807). 28) There were no clinically significant safety concerns clearly linked to the drug, confirming the good tolerability of this agent. Disease severity can be assessed noninvasively by ABI.…”
Section: Discussionmentioning
confidence: 56%